MMDH2-mediated hydroxyproline accumulation regulates iron-deficiency stress response in Arabidopsis - Xi Wu; Mengfan Wu; Qian Ma; Zhen Zhang; Junjia Sheng; Yifan Zhu; Jiena Xu; Guangna Chen; Hui Song; Shuqing Cao (Plant Stress)
Iron (Fe) deficiency represents a significant constraint on plant growth, particularly in alkaline soils where Fe bioavailability is limited. In this study, we demonstrate that mitochondrial malate dehydrogenase MMDH2 acts vitally in the response of Arabidopsis to Fe deficiency. mmdh2 mutants displayed sensitivity to the stress of Fe deficiency, while MMDH2-overexpressing lines displayed enhanced tolerance to this stress. This increased tolerance is associated with elevated Fe content, decreased accumulation of ROS, and raised transcription level of NAS4. Remarkably, the accumulation of hydroxyproline (HYP) was dramatically induced in wild-type plants under stress of Fe deficiency but was not observed in mmdh2 mutants. Exogenous supplementation with HYP restored the mmdh2-sensitive phenotype under Fe deficiency stress, suggesting that HYP is a signaling molecule that modulates the Fe deficiency response. Furthermore, we revealed that the bHLH transcription factor ILR3 binds directly to the MMDH2 promoter and activates its transcription under conditions of Fe deficiency, thereby establishing an ILR3-MMDH2 regulatory module. This study positions MMDH2 as a central hub integrating metabolic and transcriptional pathways essential for maintaining Fe homeostasis. These findings provide new insights into plant stress responses and potential strategies for enhancing crop tolerance in environments characterized by limited Fe availability.